Scientific Methods in the Study of Islamic Philosophy and Science - Hasnan Abdi; Salminawati Salminawati (Budapest International Research and Critics University, 2022)
The source of all knowledge is Allah SWT. However, this is evidenced by the verses of the Qur'an which say that knowledge comes from Allah and as a teacher (teacher). Muslim scientists are of the opinion that what Western philosophers put forward about how to acquire knowledge is not as perfect and complete as that which Allah conveys in the Qur'an. The scientific method is a method or certain steps that must be taken in order to carry out a scientific project. The scientific method can also be interpreted as a way of applying logical principles to the discovery, validation and explanation of truth. There are several scientific methods in Islam, namely the bayani method, the burhani method, the tajribi method, and the irfani method. The commentators use the bayani method in studying and exploring the knowledge contained in the Qur'an, the philosophers apply the burhani method in understanding non-physical objects, the scientists apply the tajribi method to study physical objects and the Sufis apply the irfani method to witnessing non-physical objects.